The effect of isolated core training on selected measures of golf swing performance - Weston, M.; Coleman, N. J.; Spears, I. R. (Medicine & Science in Sports & Exercise, 2013)
Purpose: This study aimed to quantify the effect of an 8-wk isolated core training program on selected ball and club parameters during the golf swing and also the variability of these measures.